Modelling human neurodegeneration using induced pluripotent stem cells - Prots, Iryna; Winner, Beate; Winkler, Jürgen (The Matrix of Stem Cell Research. An Approach to Rethinking Science in Society, 2019)
Neurodegeneration is a process of neuronal damage and death. A progressive loss of neurons is a common pathological feature of many neurodegenerative diseases, including motor neuron diseases (MND) and Parkinson's disease (PD). Neurodegenerative diseases are incurable and the only therapies possible are to this date symptomatic. Discovering the mechanisms that either lead to the disease occurrence or that influence the disease progression (together called 'pathomechanisms') would open up possibilities for developing new therapeutic approaches. Cellular material for research in the field of human neurodegeneration is very limited and mostly available as a post-mortem tissue derivate. Therefore, stem cells, as a source of different types of somatic cells, are a very promising tool for developing suitable human models to investigate neurodegeneration. With the discovery of induced pluripotent stem cells (iPSC), researchers now have access to otherwise difficult-to-obtain patient-specific cellular material to investigate the mechanisms that cause neuronal loss and that lead to the development of a neurodegenerative disease. In other words, iPSC-based technology allows the retrieving of disease-specific neurons and thereby allows the observation of the disease development in a dish. In this article, we first describe the symptomatic and current management of two big groups of neurodegenerative diseases: MND and PD. We next explain the advantages of using iPSC technology for the investigation of human neurodegeneration. Then, we highlight a number of pathomechanisms underlying neuronal degeneration in MND and PD, which have been uncovered in iPSC-based models. We finally show that some disease-related phenotypes could already be rescued on a cellular level in the laboratory and discuss the iPSC-based research as a promising tool, fuelling hope that new successful therapies for neurodegenerative disorders can be developed.
CRIS-Team Scopus Importer:2024-08-07
Keywords: Bioscience; Humanities; Medicine; Dentistry; Nursing & Allied Health; Social Sciences